Fatigue behaviour of aluminium 6061 in tailor welded blank - Wan Iryana, Wan Md Nor (2013)
Aluminium is widely used in many welding applications. 6061 aluminium alloy is one of the most common aluminium alloys in automotive industry. Welding is the permanent joining of two materials. The drive towards weight reduction in the automotive industry has led to the use of tailor- welded blanks (TWB) for structural applications. Forming of TWB is one of the challenging welding skills due to a significant reduction of formability associated with the type of blank. The different thickness combinations and compositions will give the different results to tensile test. The local approaches to fatigue have gaining added interest in the analysis of welded joints especially in TWB. In this sense, this research seeks to understand the significance of the fatigue crack initiation evaluated using a local strain-life approach, on the total fatigue life estimation for TIG welding.